Respostas
respondido por:
11
P.A = { x-r , x, x+r}
temos:
x-r + x + x+r = -12
3x = -12
x = -4
produto:
(x-r) (x) (x+r) = 420
(-4 -r) (-4) (-4 +r) = 420
(-4 -r) (r - 4) = -105
-4r + 16 -r² + 4r = -105
-r² = -105 - 16
r² = 121
r = 11
Logo, a P.A:
-4 -11, -4, -4 + 11
-15, -4 , 7 --> resposta
temos:
x-r + x + x+r = -12
3x = -12
x = -4
produto:
(x-r) (x) (x+r) = 420
(-4 -r) (-4) (-4 +r) = 420
(-4 -r) (r - 4) = -105
-4r + 16 -r² + 4r = -105
-r² = -105 - 16
r² = 121
r = 11
Logo, a P.A:
-4 -11, -4, -4 + 11
-15, -4 , 7 --> resposta
Perguntas similares
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás